Interpersonal Risk Factors for Suicide in Cocaine Dependence: Association with Self‐Esteem, Personality Traits, and Childhood Abuse. Issue 4 (6th February 2020) - Zhornitsky, Simon; Le, Thang M.; Dhingra, Isha; Adkinson, Brendan D.; Potvin, Stephane; Li, Chiang‐shan R.
Abstract : Objective: Studies have linked cocaine dependence to suicidality. According to the Interpersonal Theory of Suicide, suicidal behavior becomes likely with the simultaneous presence of perceived burdensomeness (PB), lack of (or thwarted) belongingness (TB), and acquired fearlessness about death (FAD). Here, we examined personality and other variables, including depression, self‐esteem, childhood abuse, and substance use, as predictors of these risk factors in cocaine‐dependent individuals (CDs). Methods: Seventy CDs and 70 healthy controls (HCs) participated. We examined group differences in a group‐by‐sex analysis of variance and identified predictors of PB, TB, and FAD in stepwise regressions. Results: CDs exhibited elevated PB and TB but not FAD, compared to HCs. CDs also exhibited elevated harm avoidance, novelty seeking, depression, and lower self‐esteem and reward dependence. Females reported elevated sexual abuse, harm avoidance, reward dependence, depression, but lower FAD, relative to males, among CDs and HCs. Among CDs, PB was predicted by lower self‐esteem and greater emotional abuse; TB was predicted by lower self‐esteem and reward dependence, as well as greater emotional and sexual abuse; and FAD was predicted by lower harm avoidance and greater physical abuse. Conclusions: Interventions targeting suicidality in cocaine dependence should take into consideration self‐esteem, personality traits, and childhood abuse.